Global genomic analysis reveals rapid control of a robust innate response in SIV-infected sooty mangabeys - Bosinger, Steven E.; Li, Qingsheng; Gordon, Shari N.; Klatt, Nichole R.; Duan, Lijie; Xu, Luoling; Francella, Nicholas; Sidahmed, Abubaker; Smith, Anthony J.; Cramer, Elizabeth M.; Zeng, Ming; Masopust, David; et al. (The Journal of Clinical Investigation, 2009)
Natural SIV infection of sooty mangabeys (SMs) is nonprogressive despite chronic virus replication. Strikingly, it is characterized by low levels of immune activation, while pathogenic SIV infection of rhesus macaques (RMs) is associated with chronic immune activation. To elucidate the mechanisms underlying this intriguing phenotype, we used high-density oligonucleotide microarrays to longitudinally assess host gene expression in SIV-infected SMs and RMs. We found that acute SIV infection of SMs was consistently associated with a robust innate immune response, including widespread upregulation of IFN-stimulated genes (ISGs) in blood and lymph nodes. While SMs exhibited a rapid resolution of ISG expression and immune activation, both responses were observed chronically in RMs. Systems biology analysis indicated that expression of the lymphocyte inhibitory receptor LAG3, a marker of T cell exhaustion, correlated with immune activation in SIV-infected RMs but not SMs. Our findings suggest that active immune regulatory mechanisms, rather than intrinsically attenuated innate immune responses, underlie the low levels of immune activation characteristic of SMs chronically infected with SIV.